PENGABDIAN KEPADA MASYARAKAT BERBASIS MODERASI BERAGAMA PADA KOMUNITAS ZAWIYAH SIRR EL-SA’ADAH SIDAMULYA CIREBON - Theguh Saumantri; Aah Syafaah (ABDI MAKARTI, 2023)
The purpose of this service is to provide an understanding of the importance of the attitude and practice of religious moderation in this pluralistic world. In this community service activity, it is carried out at Jam'iyyah Zawiyah Dar el-Sa'adah, which is a non-formal Islamic educational institution in the form of a community of regular recitation congregations. Activities at dedication to the community at Jam'iyyah Zawiyah Dar el-Sa'adah are carried out to form a more moderate understanding. In this community service, the participatory action research methodology is used as a strategy to achieve the goals of the service. The implementation steps used for community service are filling out lectures and presentations as references, followed by discussion. The conclusion of this activity is to shape the attitude and practice of religious moderation towards the Jam'iyyah Zawiyah Dar el-Sa'adah community in the life of the nation and state and to create harmony in social relations in various aspects of life.